2005
DOI: 10.1191/0959683605hl871ra
|View full text |Cite
|
Sign up to set email alerts
|

Aeolian sand depositional records from western Nebraska: landscape response to droughts in the past 1500 years

Abstract: The Great Plains is dominated by presently stabilized dune fields that are indicators of extreme drought in the late Holocene. This study focused on deciphering the timing of reactivation of dunes in western Nebraska. Stratigraphy adjacent to dune-dammed lakes reveals aeolian sand separated by palaeosols, indicating mobilization of aeolian sand followed by landscape stability. The chronology of aeolian-sand depositional events is constrained using the luminescence-based, single aliquot regeneration method, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 41 publications
3
62
0
Order By: Relevance
“…Holocene paleoclimatic evidence from the Nebraska Sand Hills region is predominantly derived from paleosols and eolian sediments (Stokes and Swinehart, 1997;Goble et al, 2004;Miao et al, 2007;Forman et al, 2005), as well as from a limited number of studies of wetland and marsh systems (Mason et al 1997;Nicholson and Swinehart, 2005). Optically stimulated luminescence (OSL) dating of sand and loess deposits, in conjunction with radiocarbon dates from paleosols interspersed between dune deposits, provides evidence of the timing of droughts that destabilized the dune fields in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Holocene paleoclimatic evidence from the Nebraska Sand Hills region is predominantly derived from paleosols and eolian sediments (Stokes and Swinehart, 1997;Goble et al, 2004;Miao et al, 2007;Forman et al, 2005), as well as from a limited number of studies of wetland and marsh systems (Mason et al 1997;Nicholson and Swinehart, 2005). Optically stimulated luminescence (OSL) dating of sand and loess deposits, in conjunction with radiocarbon dates from paleosols interspersed between dune deposits, provides evidence of the timing of droughts that destabilized the dune fields in the past.…”
Section: Introductionmentioning
confidence: 99%
“…OSL dating of eolian sediments in combination with radiocarbon dating of paleosols by Goble et al (2004) provided additional evidence for reactivation of dune sediments during the MCA. Forman et al (2005) found evidence from OSL dating for six reactivations during the past 1500 years at two sites in the Nebraska Sand Hills, including one potentially correlative with 16th century drought identified in other parts of the western United States. Miao et al (2007) used OSL to date eolian sediments and loess sediments from numerous sites in the central Great Plains, including the Nebraska Sand Hills, and found three major peaks of eolian activity during the last 4000 years, centered at 3.8, 2.5, and between ~1.0 and 0.7 ka.…”
Section: Timing Of Dune Reactivations In the Nebraska Sand Hillsmentioning
confidence: 99%
“…Extensive reactivation of the dune field has occurred three times in the last 4000 years, centered around 3.8, 2.5, and between ~1.0 and 0.7 ka during the MCA (Miao et al, 2007). Partial reactivations of the dunes (involving increased areas of bare sand and partial movement) have occurred since the MCA, including the 1930s Dust Bowl and other prehistoric episodes (Forman et al, 2005), but none have led to such extensive reactivation.…”
Section: Geologic Settingmentioning
confidence: 99%
See 2 more Smart Citations